The Influence of Crystallinity on the Weather Resistance of CF/PEEK Composites - Batista, Natassia L. [UNESP]; Rezende, Mirabel C.; C.Botelho, Edson [UNESP] (Springer Nature, 2021)
The purpose of this work is to investigate how the crystallinity degree of carbon fiber / poly(ether-ether-ketone (CF/PEEK) composites affects their performance when exposed to ultraviolet radiation, hygrothermal, and salt fog conditionings. Thermal characterization was performed by differential scanning calorimetry (DSC) and dynamical mechanical analyses (DMA), whereas interlaminar shear strength (ILSS), impulse excitation technique and compression tests were employed for mechanical characterization. According to the results obtained in this work, the CF/PEEK laminates with higher crystalline contents presented significantly lower water absorption. An increase in the crystallinity degree throughout the conditionings was observed for the CF/PEEK samples with lower crystalline contents, as a result of chemi-crystallization, or high temperatures, and/or water uptake. Moreover, the crystalline content also showed to affect the severity of the degradation for the UV/condensation conditioning, with the samples with lower degree of crystallinity being the most resistant. No significant changes have been observed for the mechanical properties evaluated.
Keywords: Interface; Structural composites; Thermoplastic laminates